VIGOR AND VIABILITY TEST OF CUCUMBER SEED USING NaOCl AND DIFFERENT DRYNG METHODS - Kartina Kartina; Mardhiana Mardhiana; Wiwik Karlina (Jurnal Inovasi Pendidikan dan Sains, 2021)
Cucumber is a fruit that produces seed that have pulp. The presence of pulp in the seeds can inhibit germination. This causes problem in seed production. Therefore, to remove the pulp from the seeds, it can be done by various methods such as chemical extraction or drying method. This study was aimed to determine the response of cucumber seed germination treated by NaOCl and different drying methods. This research is an experimental with a factorial Randomized Block Design (RBD), consisting of 8 treatment with 3 repetitions. The research consist of seed preparation, treatment, seeding and observation. The result show that NaOCl or drying treatment and the combination of the two treatments had no significant effect on all the variables. However, soaking with 5% NaOCl could increase the vigor index of 98,67%, the growth rate (7,69%) and the maximum growth potential of cucumber seeds up to 100% better than other treatments.